INFLUENCE OF SIBUTRAMINE, ORLISTAT AND ISPAGHULA IN REDUCING BODY WEIGHT AND TOTAL BODY FAT CONTENT IN OBESE INDIVIDUALS - Kazmi, Syed Asif J; Khan, Moosa; Mashori, Ghulam Rasool; Saleem, Azra; Akhtar, Naheed; Jahangeer, Ashraf (Journal of Ayub Medical College Abbottabad, 2009)
Background: The correlations between combined body fat parameters and risk factors of obesity explained a portion of the variation in the weight, BMI and waist circumference, the average number of categorical metabolic risk factors increases progressively with increasing total body fat content. There is currently no data available in which influence of drugs can be assessed on total body fat content. This was a non-randomized, prospective, open-label, parallel group study was conducted to compare the effectiveness of sibutramine, orlistat and ispahgula in reducing body weight and percentage of total body fat content in obese individuals. Methods: A nonrandomized, open label, prospective, intention to treat clinical trial was conducted from July 2008 to March 2009 in JPMC, Karachi, Pakistan. The study was based on three arms A (ispahgula), B (orlistat) and C (sibutramine) comprising 40 patients in each. The selection criteria has included patients from either sex with age 18 years or more with BMI ‰¥30 as obese with or without associated risk factors and BMI ‰¥27 <30 as over weight only if any significant risk factor is present. Compliance on diet chart and instruction for life style modification were assessed monthly. Results: The comparison of mean difference in percentage of total body fat content between the groups and within the groups at day 150 is (p-value) 0.029 and difference in body weight is (p-value) 0.042 which is statistically significant. Conclusion: Sibutramine is more effective than ispahgula and orlistat in reducing body weight and percentage of total body fat content in obese patients. Keywords: Sibutramine, Orlistat, Ispahgula, body weight and obesity.